Sustainable manufacturing practices: A systematic analysis and guideline for assessing the industrial Product Carbon Footprint - Gutwald, Benjamin; Baumann, Nicolas; Funk, Felix; Reichenstein, Tobias; Albayrak, Baris; Franke, Jörg (2024 1st International Conference on Production Technologies and Systems for E-Mobility, EPTS 2024, 2024)
Climate protection has gained significant political and social relevance in the corporate sphere. On the one hand, industry bears a special responsibility towards reducing greenhouse gas (GHG) emissions. On the other hand, adopting sustainable practices presents multiple economic opportunities that surpass mere image and efficiency factors. In various industries, the carbon emissions associated with specific products are becoming a crucial factor in purchasing decisions. One example is the automotive industry, where original equipment manufacturers (OEMs) are increasingly looking to track and manage the carbon footprint of their products throughout the supply chain. Moreover, regulatory requirements obligate companies to measure their products' GHG emissions. This includes the EU's Battery Passport Initiative. From 2026, all batteries installed in electric vehicles must provide basic sustainability-related information, including transparent documentation of their carbon footprint. This shows that the Product Carbon Footprint (PCF) has become a crucial business indicator, increasingly influenced by Life Cycle Assessment (LCA) methodologies. However, obstacles remain with data collection and GHG emission accounting. Comprehensive standards and guidelines exist for the quantitative determination and reporting of GHG emissions. Nonetheless, quantifying the PCF presents challenges for many companies. This is due to high complexity, insufficient data as well as diverse methodologies and the lack of a mandatory standard. Hence, a valid comparison of the results is not always feasible. This publication provides a survey and classification of various standards and software-based solutions for calculating the PCF, integrating LCA principles. The analysis' requirements profile is shaped by international regulations, economic, and political trends. To tackle the primary challenges in PCF determination, essential research trends and solutions are compiled based on a literature review. The final outcomes are presented in the form of a practical guide, assisting users in measuring, and communicating product specific GHG emissions in manufacturing throughout the supply chain.
CRIS-Team Scopus Importer:2024-08-02
Keywords: Carbon Footprint; Greenhouse Gas Protocol; ISO 14067; Life Cycle Assessment; PCF; Sustainable manufacturing